2015
DOI: 10.1159/000430458
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis in Asia: Clinical Features and Management

Abstract: Background: Lupus nephritis (LN) is a common and severe organ involvement manifesting itself in systemic lupus erythematosus (SLE). There is a considerable difference in prevalence, severity, treatment response and outcomes between Asian LN patients and LN patients from other racial backgrounds. Summary: Asian SLE patients have a higher prevalence of LN than Caucasian SLE patients and often present with a more severe disease. Increasing data from genetic studies, accompanied by progress in high-throughput geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 74 publications
(113 reference statements)
6
66
0
2
Order By: Relevance
“…In contrast, 5‐year renal survival ranged between 48% and 84% in Africans . These results and our own confirm the general consensus that Asians with LN have favourable outcomes . Ethnicity also appeared to influence outcomes within our multi‐ethnic cohort as Chinese were more likely to have complete remission and less likely to develop progressive CKD, although the difference did not reach statistical significance ( P = 0.07).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In contrast, 5‐year renal survival ranged between 48% and 84% in Africans . These results and our own confirm the general consensus that Asians with LN have favourable outcomes . Ethnicity also appeared to influence outcomes within our multi‐ethnic cohort as Chinese were more likely to have complete remission and less likely to develop progressive CKD, although the difference did not reach statistical significance ( P = 0.07).…”
Section: Discussionsupporting
confidence: 73%
“…27 These results and our own confirm the general consensus that Asians with LN have favourable outcomes. 6,16 Ethnicity also appeared to influence outcomes within our multi-ethnic cohort as Chinese were more likely to have complete remission and less likely to develop progressive CKD, although the difference did not reach statistical significance (P = 0.07). It has been postulated that blacks may be genetically predisposed to more severe lupus phenotypes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The most recent American College of Rheumatology guidelines also specifically suggest lower doses of mycophenolate mofetil as induction therapy for class III/IV lupus nephritis in Asian patients based on evidence from the Far East. 13 Asia has also taken the lead in the study of emerging approaches in novel treatment approaches to SLE and lupus nephritis, 14 such as the combination of cyclophosphamide with mycophenolate mofetil for induction, 15 as well as the use of tacrolimus and its use in 'multitarget therapy' for induction and maintenance of lupus nephritis, all with promising results. [16][17][18][19] The concept of interleukin 2 (IL-2) therapy for various immune-mediated diseases has also kindled much interest over the past few years, and He et al recently demonstrated the clinical efficacy of low-dose recombinant human IL-2 in CD4 + T cell modulation and improving disease activity in 38 SLE patients in China.…”
Section: Introductionmentioning
confidence: 99%